Monitoring of the efficacy of multidrug therapy (MDT) by polymerase chain reaction (PCR) and, Mycobacterium leprae particle agglutination (MLPA) test in leprosy patients (Faculty of Medicine Universitas Indonesia, 1997)
[no abstract available]